19
Аноним
Математика
09 марта 12:49

1.) Разложите на множители выражение (b-4)²-(a+3)²:A. (b-a-7)(b-a+1)B. (b-a-7)(b+a-1)C. (b+a-7)(b-a+1)D. (b-a+7)(b-a-1)2.)

Разложите на множители выражение A. (x³-y²)(x³+y²)B. x²(x²-y²)²C. x²(x²+y²)²D. x²(x²-y²)(x²+y²)

Ответ или решение1

1) (b - 4)^2 - (a + 3)^2 = b^2 - 8b + 16 - (a^2 + 6a + 9) = b^2 - 8b + 16 - a^2 - 6a - 9 = b^2 - 8b - a^2 - 6a + 7.

A. (b - a - 7)(b - a + 1) = b^2 - ab + b - ab + a^2 - a - 7b + 7a - 7 = b^2 - 2ab - 6b + a^2 + 6a - 7.

B.  (b - a - 7)(b + a - 1) = b^2 + ab - b - ab - a^2 + a - 7b - 7a + 7 =  b^2 - 8b - a^2 - 6a + 7.

C. (b + a - 7)(b - a + 1) = b^2 - ab + b + ab - a^2 + a - 7b + 7a - 7 = b^2 - 6b - a^2 + 8a - 7.

D. (b - a + 7)(b - a - 1) = b^2 - ab - b - ab + a^2 + a + 7b - 7a - 7 = b^2 - 2ab + 6b + a^2 - 6a - 7.

Ответ: В.

 2) А. (x^3 - y^2)(x^3 + y^2) = x^6 - y^4.

B. x^2(x^2 - y^2) = x^4 - x^2y^2.

C. x^2(x^2 + y^2) = x^4 + x^2y^2.

D. x^2(x^2 - y^2)(x^2 + y^2)= x^2(x^4 - y^4) = x^6 - x^2y^4.

0 / 10000
ВходРегистрация

Вход

или

Регистрация